Homoplantaginin exerts therapeutic effects on intervertebral disc degeneration by alleviating TNF-α-induced nucleus pulposus cell senescence and inflammation - Jiadong Guo; Pu Zhang; Xiao Yang; Xin Wang; Xiankun Cao; Jie Zhao (Frontiers in Pharmacology)
The incidence of intervertebral disc degeneration (IDD) is increasing year by year, while the age of onset of IDD is decreasing year by year. For the individuals affected by IDD, an alternative treatment to surgery is required. IDD is thought to be related to nucleus pulposus (NP) cell senescence and inflammation. Therefore, inhibition of NP cell inflammation and senescence may counteract IDD. We screened 20 small-molecule drugs to compare their anti-inflammatory effects, and finally selected homoplantaginin (HPG) as a treatment regimen. HPG is an extract of Salvia miltiorrhiza with anti-inflammatory properties. The objective of this research was to investigate if HPG could have a therapeutic effect on IDD through its anti-inflammatory or anti-aging effects. We identified the appropriate concentration of HPG in primary NP cell cultures and demonstrated that it inhibited inflammatory pathway activation and reduced the senescence phenotype of NP cells in vitro. And in vivo, the therapeutic effect of HPG on caudal disc degeneration was confirmed consistently. In conclusion, our findings suggest that HPG can alleviate the degeneration in the pathogenesis of IDD and that it has a potential effect in the treatment of IDD.